The Gilets Jaunes: A Symptomatic Conflict in a 'Class Society Without Classes' - vom Bruch, Jorin (Momentum Quarterly, 2021)
The protest movement of the Gilets Jaunes is analyzed as a specifically post-Fordist class conflict. Based on the conceptual tools of Marxian class theory, empirically supported theses about the characteristics of the movement are formulated. The protest of the Gilets Jaunes against the increase of the gasoline tax articulates economically based existential fears that are shared by large parts of the working class. The militant demonstrations, the blockades of the traffic circles and the heterogeneous expressions of the demonstrators indicate an unusual form of conflict. It is shown that the neoliberal reorganization of French society through the precarization of the world of work, the fragmentation of industrial relations, and an increasing socio-spatial polarization favors the emergence of "non-normative" conflicts. While - beyond the example of France - structural class differences gain in importance, institutionalized forms of processing social inequality remain largely marginalized. Taken together, this results in the contradictory picture of a class society that is not aware of its own movement dynamics. Against this background, the question of starting points for a trade union practice is discussed.
Keywords: class conflict; yellow vests; postfordism; class theory; trade unions